Evaluation and development of flood‐tolerant soybean cultivars. (2nd November 2017) - Wu, Chengjun; Zeng, Ailan; Chen, Pengyin; Hummer, Wade; Mokua, Jane; Shannon, J. Grover; Nguyen, Henry T.
Abstract: Soybean ( Glycine max [L.] Merr.) cultivars are generally sensitive to flooding stress. The plant growth is severely affected and grain yield is largely reduced in the flooded field. It is important to develop flood‐tolerant soybean cultivars for grain production in regions of heavy rainfalls worldwide. In this study, a total of 722 soybean genotypes were evaluated for flooding tolerance at R1 stages (first flower at any node) in the 5‐year flooding screening tests. Differential soybean genotypes exhibited diverse responses to flooding stress with that plant foliar damage score (FDS) and plant survival rate (PSR) ranged from 1.9 to 8.8 and 3.4% to 81.7%, respectively ( p  < .0001). Based on our standard of flooding evaluation, most genotypes were sensitive to flooding with 6.0 of average FDS and 38.7% of PSR. Fifty‐two soybean genotypes showed flooding tolerance and 11 genotypes were with consistent flooding tolerance during 4‐ to 5‐year continual evaluations. In the meantime, six genotypes were identified with consistent high sensitivity to flooding. The group analysis showed that genotypes from different sources had distinguishable responses to flooding stress ( p  < .0001). The interacting analysis of year and flooding tolerance indicated that FDS and PSR means were significantly different among 5 years due to weather temperature and flooding treatment time influences of each year ( p  < .0001). Furthermore, five breeding lines with high‐yielding and flood‐tolerant traits were developed using selected consistent flood‐tolerant and high‐yielding genotypes through conventional breeding approach.